2016
DOI: 10.18240/ijo.2016.05.11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two different methods of preoperative marking for toric intraocular lens implantation: bubble marker versus pendulum marker

Abstract: Both preoperative marking techniques result in approximately 3 of alignment error. Both marking techniques are simple, predictable, reproducible and easy to perform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Woo et al performed a prospective comparative study to assess the accuracy of three horizontal meridian marks using the iTrace system and found that the average rotational deviation of horizontal marking ranged from −0.66° to 2.2° [ 10 ]. Farooqui et al compared the accuracy of a bubble marker with that of a pendulum marker and found that the mean absolute alignment error for both techniques was similar and less than 3° [ 11 ]. Igarashi et al assessed the horizontal meridian misalignment of limbal marking under a slit-lamp microscope and showed the axis misalignment by an average of 3.4° to 6.9° [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Woo et al performed a prospective comparative study to assess the accuracy of three horizontal meridian marks using the iTrace system and found that the average rotational deviation of horizontal marking ranged from −0.66° to 2.2° [ 10 ]. Farooqui et al compared the accuracy of a bubble marker with that of a pendulum marker and found that the mean absolute alignment error for both techniques was similar and less than 3° [ 11 ]. Igarashi et al assessed the horizontal meridian misalignment of limbal marking under a slit-lamp microscope and showed the axis misalignment by an average of 3.4° to 6.9° [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Farooqui et al . [ 6 ] compared the preoperative bubble marker versus the pendulum marker and reported both to be equally comparable, simple, predictable, reproducible, and easy to perform. Popp et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is also challenging to identify the true 3- and 9-o’clock positions. Farooqui et al 13 recently described two novel methods for marking the limbus, namely, the “bubble” and the “pendulum”, in an effort to make horizontal marks in proximity to the 3- and 9-o’clock positions. These authors observed an average misalignment of 3° with each of their novel methods; however, we must note the several problems associated with these methods and all methods that use ink to mark the limbus.…”
Section: Discussionmentioning
confidence: 99%